UPAYA GURU IPS DALAM MEMBENTUK KARAKTER BERTANGGUNG JAWAB SISWA KELAS VIII C MTS HASYIM ASY’ARI BATU - Pratiwi, Anisah Novita Tia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Responsible character education is the attitude and behavior of a person to carry out their duties and responsibilities as themselves, society, environment, country, and God. The formation of the character of trust can be applied through the activities of internal and external learning. Responsibility is an attitude that must be formed so that students can be accountable for what they have done. The purpose of this study was to: (1) find out the character forms responsible for class VIII C MTs Hasyim Asy'ari Batu (2) to find out the efforts of social studies teachers informing capable characters of class VIII MTs Hasyim Asy'ari Batu (3) know what factors encourage and hinder the formation of role responsible for class VIII C MTs Hasyim Asy'ari Batu. The research method used is a qualitative approach with a type of case study research. Data collection uses observation, interviews, and documentation. The results of the study show that, (1) Character forms are responsible for students namely always doing school work well, attending congregational prayers in school and punishments for those who violate school rules by using persuasive approaches and giving examples in their daily lives (2 ) The implementation of character formation is responsible to be carried out in the classroom and outside the classroom. Application through habituation by the teacher (3) There are driving and inhibiting factors in the way the character formation is responsible for class VIII C students at MTs Hasyim Asy'ari Batu. One of them is habituation carried out by the school and teacher teachers, and also one of the inhibiting factors here is about environmental factors that do not support the attitude of responsibility.Keywords: The character of Responsibility, Integrated Social Studies